Intrinsically shunted Josephson junctions for electronics applications - Belogolovskii, M.; Zhitlukhina, E.; Lacquaniti, V.; Leo, N. De; Fretto, M.; Sosso, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Conventional Josephson metal-insulator-metal devices are inherently underdamped and exhibit hysteretic cur-rent-voltage response due to a very high subgap resistance compared to that in the normal state. At the same time, overdamped junctions with single-valued characteristics are needed for most superconducting digital applications. The usual way to overcome the hysteretic behavior is to place an external low-resistance normal-metal shunt in parallel with each junction. Unfortunately, such solution results in a considerable complication of the circuitry design and introduces parasitic inductance through the junction. This paper provides a concise overview of some generic approaches that have been proposed in order to realize internal shunting in Josephson heterostructures with a barrier that itself contains the desired resistive component. The main attention is paid to self-shunted devices with local weak-link transmission probabilities that are so strongly disordered in the inter-face plane that transmission probabilities are tiny for the main part of the transition region between two super-conducting electrodes, while a small part of the interface is well transparent. We discuss the possibility of realizing a universal bimodal distribution function and emphasize advantages of such junctions that can be considered as a new class of self-shunted Josephson devices promising for practical applications in superconducting electronics operating at 4.2 K.